Towards effective inventory management of health commodities at service delivery points: A case of health personnel in Shamva District, Zimbabwe. - Rodgers, Kunaka Taurayi; Desderio, Chavunduka M. (Archives of Business Research, 2020)
Despite much effort at improving availability of health commodities, stock-outs and expiries are still commonplace at service delivery centres. The success of any inventory management programme relies on the people undertaking it and there seems to be a missing link in the supply chain that could be related to the people tasked with inventory management at service delivery points. The study thus sought to assess whether the personnel’s knowledge, attitude, perceptions and practices are the missing link resulting in stock-outs and expires. The study employed a mixed method approach wherein quantitative and qualitative data collection methods were employed. The data collected sought to explore various aspects of the personnel including the training facility regarding inventory management, personal attitudes and, perceptions and practices towards certain inventory management aspects. Clearly it was found that personnel knowledge levels were very low, attitudes and perceptions veer in the negative whilst practices are not up to standard. This correlated to the availability of drugs and commodities at service delivery points.